2020
DOI: 10.1039/d0sc02542a
|View full text |Cite
|
Sign up to set email alerts
|

Ru-catalyzed isomerization of ω-alkenylboronates towards stereoselective synthesis of vinylboronates with subsequent in situ functionalization

Abstract: A regio- and stereoselective ruthenium-catalyzed isomerization of ω-alkenyl boronates into stereodefined di- and trisubstituted alkenylboronate derivatives is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 118 publications
0
12
0
Order By: Relevance
“…Subsequently, the same group disclosed a related sequential catalytic isomerization/Suzuki cross-coupling strategy in which the vinyl boronic ester intermediates generated via isomerization act as a transmetalating agent rather than electrophilic coupling partner. 55 Overall, 1,2-disubstituted styrenes were prepared with similar efficiency and stereocontrol than with the sequential alkenyl ether isomerization/Kumada crosscoupling approach.…”
Section: Sequential Processesmentioning
confidence: 96%
“…Subsequently, the same group disclosed a related sequential catalytic isomerization/Suzuki cross-coupling strategy in which the vinyl boronic ester intermediates generated via isomerization act as a transmetalating agent rather than electrophilic coupling partner. 55 Overall, 1,2-disubstituted styrenes were prepared with similar efficiency and stereocontrol than with the sequential alkenyl ether isomerization/Kumada crosscoupling approach.…”
Section: Sequential Processesmentioning
confidence: 96%
“…From the vantage point of feedstock accessibility, this transformation is highly desirable because the starting materials can be readily generated from vinyl halides . The past decade has seen the emerging of transition-metal catalyzed regio- and stereoselective isomerization of monosubstituted terminal alkenes to internal olefins. , In contrast, examples of the isomerization of 1,1-disubstituted alkenes into trisubstituted alkenes (1,1-di-to-trisubstitution isomerization) remain elusive and scattered, which can be in part attributed to the difficulty associated with the generation of metal quaternary alkyl complexes, the prerequisite catalytic intermediates if the isomerization occurs through the metal-hydride insertion elimination mechanism . Within this category, in 2017, Trost reported that a Ru­(II) complex catalyzes the isomerization of 1,1-disubstituted alkenyl boronates bearing an amide functionality at the allylic positions to furnish trisubstituted enamides with excellent stereoselectivity (Scheme c) .…”
Section: Introductionmentioning
confidence: 99%
“…Such a strategy has been explored by Suginome in the isomerization of boronate esters derived from the silaboration and diboration of terminal alkynes, where highly substituted alkenyl­boronate esters were generated from readily available starting materials (Scheme d) . In this context, our group has recently demonstrated that ω-ene alkylboronate esters can undergo long-range isomerization in the presence of a Ru–H catalyst to result in stereodefined alkenyl­boronate esters (Scheme e) . In line with our interest in the utilization of alkene isomerization in stereoselective synthesis, we set out to explore the alkene isomerization of readily available 1,1-disubstituted alkenyl­boronates into either ( E )- or ( Z )-trisubstituted alkenyl­boronate esters (Scheme g).…”
mentioning
confidence: 92%
“… 28 In this context, our group has recently demonstrated that ω-ene alkylboronate esters can undergo long-range isomerization in the presence of a Ru–H catalyst to result in stereodefined alkenylboronate esters ( Scheme 1 e). 29 In line with our interest in the utilization of alkene isomerization in stereoselective synthesis, 30 36 we set out to explore the alkene isomerization of readily available 1,1-disubstituted alkenylboronates 37 40 into either ( E )- or ( Z )-trisubstituted alkenylboronate esters ( Scheme 1 g). Overall, this strategy would offer selective access to both stereoisomers of the target alkenylboronate esters from a single starting material.…”
mentioning
confidence: 99%